2016
DOI: 10.1016/j.rbre.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Swimming and cycling do not cause positive effects on bone mineral density: a systematic review

Abstract: Osteoporosis is considered a common metabolic bone disease and its prevalence is increasing worldwide. In this context, physical activity has been used as a non-pharmacological tool for prevention and auxiliary treatment of this disease. The aim of this systematic review was to evaluate the effects of cycling and swimming practice on bone mineral density (BMD). This research was conducted in accordance with the recommendations outlined by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 34 publications
2
20
1
5
Order By: Relevance
“…This study reported a non‐significant difference in total bone mineral density between the control and the exercise group after the intervention . Consistent with our results, some studies did not find an increase in total bone mineral density in post‐menopausal women after a moderate‐intensity aerobic exercise intervention . In our study, we found a decrease in total bone mineral density, and one possible explanation could be related to the amount of mechanical loading and muscle tension that is needed to increase bone mass .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study reported a non‐significant difference in total bone mineral density between the control and the exercise group after the intervention . Consistent with our results, some studies did not find an increase in total bone mineral density in post‐menopausal women after a moderate‐intensity aerobic exercise intervention . In our study, we found a decrease in total bone mineral density, and one possible explanation could be related to the amount of mechanical loading and muscle tension that is needed to increase bone mass .…”
Section: Discussionsupporting
confidence: 90%
“…35 Consistent with our results, some studies did not find an increase in total bone mineral density in post-menopausal women after a moderate-intensity aerobic exercise intervention. 26,36 In our study, we found a decrease in total bone mineral density, and one possible explanation could be related to the amount of mechanical loading and muscle tension that is needed to increase bone mass. 11 The majority of women in this study chose to walk, 22 which has been shown to be an insufficiently strong stimulus to help preserve bone mineral density.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…However, the question arises whether Masters sport swimming is certainly good for older athletes strength and health? Abrahin's et al (2016) results showed that swimming has no positive influence on bone mineral density. Banias and Rasadean (2011) highlighted the reduction of swimming speed in relation to age, in freestyle men events.…”
Section: Introductionmentioning
confidence: 91%
“…Guadalupe-Grau, Fuentes, Guerra, & Calbet (2009) 4 reported that exercise increases peak of bone mass. However, non-weight bearing activities such as swimming and cycling exert little influence on bone mineral density (BMD) 5 , and are thus not suitable for prevention and treatment of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%